Abnormal Effects in Irradiated Carbon Materials and Associated Composites - D.I. Shvets (Adsorption Science & Technology)
The radiation/chemical modification of carbon and the use of the resulting material either alone or in association with other components in various compositions has been undertaken in an attempt to improve existing materials or to create new materials with enhanced operating characteristics. This article presents new information concerning various peculiarities in the physicochemical and mechanical properties of such materials. A mechanism for the radiation/chemical transformations in the various heterogeneous systems studied is proposed and it is shown that the results obtained may be employed for improving radiation/technological processes in the creation of new materials for advanced technological use.